A Freirean deconstruction of online education in Algeria - Sarnou, Dallel (Cadernos CIMEAC, 2022)
In his seminal and highly influential work Pedagogy of the Oppressed (1970), the Brazilian scholar Paulo Freire refers to education as “becoming an act of depositing, in which the students are the depositories and the teacher is the depositor.” Freire strongly criticizes what he calls “the banking model” of education, whether in schools colleges or universities. This model of pedagogy is prevalent and dominant in many countries of the world, and in Algeria–the country under focus in this paper. Nonetheless, with the many advanced technologies that are being integrated into educational institutions all over the world with the aim of building a more learner-centered pedagogy, Freire’s claims and views have recently been subject to many re-readings and revisions by contemporary educators. More particularly, on the recent attempts of the last couple of years to shift into online education so as to save the learning and teaching processes during the confinement imposed by the COIVD 19 pandemic, much ink has been spilled regarding the sudden and forced appliance of MOODLE platform in Algeria. The latter, as will be argued throughout this paper, is nothing but a re-incarnation of Freire’s banking model. Therefore, a pivotal query in the present paper is to unveil how online education in Algeria applied since the outbreak of the Corona pandemic does correspond to Freire’s Pedagogy of the Oppressed where the oppressed is always the learner.